A karstic model of the generation of tablelands landscapes in sandstones in Eastern Amazonia. (March 2022) - Barreto, H.N.; Braucher, R.; Salgado, A.A.R.; Siame, L.; Léanni, L.; Auler, A.; Martins, F.P.; Bourlès, D.L.
Abstract: Tablelands are typical reliefs in many cratons of the world, particularly in the eastern portion of South America. Until recently, tablelands have been interpreted as resulting from initial superficial fluvial erosion that segmented wide plateaus and subsequent slope retreat that decreased plateau areas into smaller mesas and buttes. Based on morphological observations and isotopic measurements in sandstone caves in Brazil, we present an alternative scenario in which such sandstone landscapes may result from karst processes. This study relies on cosmogenic nuclide pair concentrations ( 10 Be and 26 Al) measured in river-borne, modern fluvial sediments, suggesting that these fluvial sediments may have actually undergone complex exposure-burial histories. Collapse of cave ceilings and associated karst processes in sandstones may thus represent an initial step responsible for the morphogenesis of the regional tablelands landscape. The widespread occurrence of similar karst geoforms in tablelands in several areas in eastern/northern South America suggests that this model may have a general implication. Highlights: The morphogenesis of the tablelands landscape can have relation with karst geoforms. The tablelands can be formed by surface and subsurface fluvial processes. River sediments in Eastern Amazonian show a complex burial exposure history.